Sporophytic control of pollen meiotic progression is mediated by tapetum expression of ABORTED MICROSPORES. (25th May 2022) - Tidy, Alison C; Ferjentsikova, Ivana; Vizcay-Barrena, Gema; Liu, Bing; Yin, Wenzhe; Higgins, James D; Xu, Jie; Zhang, Dabing; Geelen, Danny; Wilson, Zoe A
Abstract : The tapetum transcription factor ABORTED MICROSPORES is key to tapetum–meiocyte crosstalk by enabling late meiosis progression, cytokinesis, radial microtubule array organization, and callose deposition. Abstract: Pollen development is dependent on the tapetum, a sporophytic anther cell layer surrounding the microspores that functions in pollen wall formation but is also essential for meiosis-associated development. There is clear evidence of crosstalk and co-regulation between the tapetum and microspores, but how this is achieved is currently not characterized. ABORTED MICROSPORES (AMS), a tapetum transcription factor, is important for pollen wall formation, but also has an undefined role in early pollen development. We conducted a detailed investigation of chromosome behaviour, cytokinesis, radial microtubule array (RMA) organization, and callose formation in the ams mutant. Early meiosis initiates normally in ams, shows delayed progression after the pachytene stage, and then fails during late meiosis, with disorganized RMA, defective cytokinesis, abnormal callose formation, and microspore degeneration, alongside abnormal tapetum development. Here, we show that selected meiosis-associated genes are directly repressed by AMS, and that AMS is essential for late meiosis progression. Our findings indicate that AMS has a dual function in tapetum–meiocyte crosstalk by playing an important regulatory role during late meiosis, in addition to its previously characterized role in pollen wall formation. AMS is critical for RMA organization, callose deposition, and therefore cytokinesis, and is involved in the crosstalk between the gametophyte and sporophytic tissues, which enables synchronous development of tapetum and microspores.